Strategi Penguatan Moderasi Beragama Berbasis Kecerdasan Buatan pada Komunitas Compok Literasi Digital - Dwijayanti, Novia Shafa; Firnanda, Aldi (re-JIEM (Research Journal of Islamic Education Management), 2026)
Digital transformation has brought about changes in diversity. This demands a strategy to strengthen religious moderation that is adaptable to technological developments thru the utilization of artificial intelligence. This research aims to analyze strategies for strengthening religious moderation thru the utilization of artificial intelligence, improvement, participation, and identifying obstacles that arise in the implementation process within the Compok Literasi community. This research uses a descriptive qualitative method. Data collection techniques include in-depth interviews, participant observation, and drawing conclusions. The research results indicate that artificial intelligence plays an active and effective role as an educational medium for religious moderation, values thru participatory learning and the constructive production of religious content. The use of artificial intelligence fosters ethical awareness within communities, particularly in filtering religious information and preventing the spread of intolerant narratives in the digital space. This research provides theoretical benefits as a relevant and applicable model for strengthening religious moderation in the digital age.